In-Built Coolant Cooling System - Gandhi, Vaibhav (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
The objective of this paper is to present the new technologies, innovations and trends in the area of automobile cooling and automobile air conditioning and cooling system, which is fast and very effective. The advancement in the field of aerodynamics and the engine management system has made the modern vehicles and automobile much faster as compare to the vehicles and automobiles of previous generations. In the modern era, the engine size is comparatively smaller and advanced for reaching the higher speed and torque requirement. As the engines of the new era become advanced, the speed and the power generation and the torque production are also high. And due to the higher power generation and the speed accessibility, the temperature of the engine becomes very high. It is increased when engine is in the running state. It creates many problems in the engine and can be dangerous for vehicle. For conquering this problem a cooling system is installed in our vehicles called Radiator which cools engine (working on the previous cooling management system) but as the above description said the advancements are done as the new generation comes. So we have to require the advanced cooling system and devices for better performance of the engine as well as the vehicle.